Globalization and divergent constructs of childhood and valuable knowledge: Influences on expectations for young children in post-colonial rural southern Tanzania. Issue 4 (December 2022) - Edwards, Laura
Childhood is a complex and socially constructed process with implications on the education of young children with issues of globalization as a powerful influence. This article presents a critical analysis of a focused ethnographic study in post-colonial rural southern Tanzania and argues a way forward in the global dialogue regarding the construction of diverse childhoods through the education of young children to balance these influences. Data was collected in rural villages of southern Tanzania including interviews, focus groups, observations from over 150 people and government and NGO policy analysis. This paper responds to the research question: whose constructs of childhood influence the opportunities young children have to learn in Ndogo villages? The larger study addresses additional significant questions and data. A critical analysis indicates decision makers, such as international donors and NGO's, impose global influences on young children's opportunities to learn by prioritizing resources for what they as outsiders' value as knowledge. Although parents and local community members are essential members of a child's life, their constructs of childhood are not valued and therefore, are either ignored or actively omitted from formal opportunities children have to learn. The findings urge scholars, NGOs, and policymakers to equally value different perspectives held by parents and community members regarding the substance of what is valuable knowledge.